2022
DOI: 10.3389/feart.2022.923252
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Water Budget of the Upper Blue Nile River Basin With Water and Energy Processes (WEP) Model

Abstract: Understanding the spatial and temporal distributions and variations of basin water budget components is essential for effective water resources management. Due to a lack of basic hydro-meteorological information, the Upper Blue Nile River Basin (UBNRB) remains poorly understood in quantifying its hydrologic fluxes and associated dynamics. This study used a physically based distributed hydrologic model, WEP. We used multi-year land use information to better estimate the water budget components (evapotranspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In Table 5, it can be seen that all of the annual water balance components with a higher value are observed during the highest rainy year (2010), whereas, in dry years in which the rainfall is below average (2002, 2004, 2008, 2009, 2011, and 2013), the contribution of water balance components to the water budget decreased significantly. Previous studies in the upper Blue Nile of Ethiopia [74,75] have shown the same trend in that the contribution of water balance components declined with the fall of rainfall.…”
Section: Annual Water Balance Componentssupporting
confidence: 60%
See 1 more Smart Citation
“…In Table 5, it can be seen that all of the annual water balance components with a higher value are observed during the highest rainy year (2010), whereas, in dry years in which the rainfall is below average (2002, 2004, 2008, 2009, 2011, and 2013), the contribution of water balance components to the water budget decreased significantly. Previous studies in the upper Blue Nile of Ethiopia [74,75] have shown the same trend in that the contribution of water balance components declined with the fall of rainfall.…”
Section: Annual Water Balance Componentssupporting
confidence: 60%
“…A study in the Hormat-Golina River of Ethiopia using the WetSpass model showed that about 68% of precipitation is lost through evapotranspiration [77]. The simulated results from the WEP modeling in the upper Blue Nile of Ethiopia showed that evapotranspiration accounts for a major share (58%) of the total rainfall [74]. In [78], the JGrass-NewAge model system was applied in the upper Blue Nile and found that evapotranspiration accounts for a major share (56%) of the total rainfall.…”
Section: Annual Water Balance Componentsmentioning
confidence: 99%
“…For instance Ref. [ 21 ], has used a distributed water and energy model (WEP) to estimate the water budget of upper BNB. The study by Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The mean annual minimum and maximum temperature over the BNB has increased from 12.69 to 13.32, 26.43 to 26.91, and from 1981 to 2010 [ 20 ]. A recent water balance study of the basin reveals that evapotranspiration (ET) accounts for 58 % of the annual water budget [ 21 ]. The average basin scale ET from 1992 to 2014, estimated by Ref.…”
Section: Methodsmentioning
confidence: 99%
“…In the UBN basin, the estimation of individual components of the hydrological cycle, such as P (Abebe et al, 2020;Abera et al, 2016;Ayehu et al, 2018;Bayissa et al, 2017;Dinku et al, 2011;Lakew et al, 2017;Lakew et al, 2020;Worqlul et al, 2018), ET (Allam et al, 2016;Weerasinghe et al, 2020), and TWS (Seyoum, 2018;Shamsudduha et al, 2017), using remote sensing are examined, whereas other research papers have studied the UBN basin using the water balance model (Abebe et al, 2022;Conway, 1997;Johnson Peggy and Curtis, 1994;Kim and Kaluarachchi, 2009;Mishra and Hata, 2006;Steenhuis et al, 2009;Tekleab et al, 2011).…”
Section: Introductionmentioning
confidence: 99%